Influence of Moisture on the Shakedown Behavior of Fine Soils for Sustainable Railway Subballast Layers - William Wilson dos Santos; Gleyciane Almeida Serra; Lisley Madeira Coelho; Sergio Neves Monteiro; Gabriel de Carvalho Nascimento; Antônio Carlos Rodrigues Guimarães (Infrastructures, 2025)
This study investigates the influence of moisture on the mechanical behavior of fine soil mixtures from the São Luís region, applied as subballast layers in railway track structures. Two samples were analyzed: a non-lateritic sandy soil (NA’, AM03) and a lateritic clayey soil (LG’, AM09). The research included physical and chemical characterization tests, as well as repeated load triaxial tests to determine the resilient modulus and shakedown limits, complemented by numerical simulations using the SysTrain 2.0 software. The samples showed average resilient modulus values of 577 MPa and 638 MPa, respectively. Tests were conducted under optimum moisture content and under moisture 1% above the optimum, induced by capillary rise in compacted samples. The results indicated that under 1% above optimum moisture, the shakedown limits were reduced by up to 50% for AM03 and 25% for AM09, demonstrating greater stability for the lateritic soil. In addition, it was observed that as stress ratios increased, the shakedown limits for both moisture conditions tended to converge. Numerical simulations confirmed the adverse influence of increased moisture on the occurrence of shakedown in both samples. For AM03, the simulations revealed progressive failure under elevated moisture, indicating a more severe stress redistribution within the subballast layer. In contrast, AM09 remained within the shakedown regime under both conditions, although it exhibited higher values of <semantics>S1/S1max</semantics> under moisture above optimum, suggesting a greater tendency toward plastic creep. These findings highlight the critical importance of moisture control for the sustainable performance of railway substructures. This study contributes to understanding environmental vulnerability in transportation infrastructure and supports the development of more resilient and sustainable railway systems.